2020
DOI: 10.1002/csc2.20333
|View full text |Cite
|
Sign up to set email alerts
|

Wild carrot diversity for new sources of abiotic stress tolerance to strengthen vegetable breeding in Bangladesh and Pakistan

Abstract: Crop wild relatives (CWRs) of carrot (Daucus. carota L.) including 64 germplasm accessions of D. carota L. subsp. carota, D. carota L. subsp. capillifolius (Gilli) Arbizu, and D. carota L. subsp. gummifer (Syme) Hook. f., as well as two accessions of another 18‐chromosome species, D. syrticus Murb., were grown in field trials to flowering under conditions of heat, drought, and salinity stress in Bangladesh and Pakistan. Plant growth before floral initiation was evaluated and plants were allowed to progress to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Tunisia lies in the centre of origin of carrot (Daucus carota) and hosts a rich diversity of wild and rare related taxa (Mezghani et al 2019;Simon et al 2020) 2019). However, it must be observed that Eleven CWR taxa (high priority) belonging to Aegilops L. (GP2) and Triticum L. (GP1b), and 6 tertiary gene pool taxa (medium priority) are relatives of wheat (Triticum spp.)…”
Section: Priority Taxamentioning
confidence: 99%
“…Tunisia lies in the centre of origin of carrot (Daucus carota) and hosts a rich diversity of wild and rare related taxa (Mezghani et al 2019;Simon et al 2020) 2019). However, it must be observed that Eleven CWR taxa (high priority) belonging to Aegilops L. (GP2) and Triticum L. (GP1b), and 6 tertiary gene pool taxa (medium priority) are relatives of wheat (Triticum spp.)…”
Section: Priority Taxamentioning
confidence: 99%
“…Культурная морковь, вероятно, была одомашнена в Центральной Азии примерно 1100 лет назад [19]. Во многих регионах мира, где выращивают морковь, популяции дикой моркови можно найти в непосредственной близости от полей культивируемой моркови [20,21].…”
Section: вестникunclassified
“…Although CWR have been relatively neglected for decades [ 15 ], their potential was highlighted by Vavilov, and their use in breeding has been increasing since the 1980s [ 16 ]. The use of CWR is widespread and well-established for crops such as barley [ 17 ], potato [ 18 ], wheat [ 19 , 20 , 21 , 22 ] and rice [ 23 , 24 , 25 ] and developing for others such as alfalfa [ 26 ], carrot [ 27 ], chickpea [ 28 ], eggplant [ 29 , 30 ], finger millet [ 31 ], grass pea [ 32 ] and sorghum [ 33 , 34 ]. The starting point for use is viable hybridization between the crop and a wild relative.…”
Section: Introductionmentioning
confidence: 99%